105 Decreases in Blood Pressure During Endovascular Stroke Therapy Are Common and Associated With Poor Functional Outcome. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Mampre, David; Wang, Anson; Sheth, Kevin; Tan, Can Ozan; Hebert, Ryan M; Matouk, Charles C; Petersen, Nils
Abstract: INTRODUCTION: Due to impaired cerebral autoregulation, blood pressure management during acute ischemic stroke is critical for avoiding secondary neurological injury and poor outcomes. However, questions concerning optimal management of blood pressure (BP) levels during endovascular therapy (EVT) remain unanswered. This study sought to examine the effect of reductions in BP and sustained hypotension during EVT on functional outcome. METHODS: We prospectively enrolled patients with acute large-vessel occlusion ischemic stroke undergoing EVT at Yale-New Haven Hospital. Intraprocedural SBP was monitored using a noninvasive BP cuff or an intra-arterial catheter. ? SBP was calculated as the difference between admission SBP and lowest SBP during EVT. Sustained relative hypotension was measured as the area between admission SBP and continuous measurements of intraprocedural SBP (aSBP). Associations with functional outcome assessed using the modified Rankin Scale (mRS) at discharge and 90 d (unfavorable outcome = 3) were assessed using ordinal and binary logistic regression. RESULTS: One hundred-twenty patients (mean age 72 ± 14, 69 F, mean NIHSS 18) were included in the study, 79 of which had 90-d outcomes. Mean admission SBP was 153 mm Hg. 92% of patients experienced ? SBP reductions during EVT (mean 46 ± 30 mm Hg). Median ? SBP among patients with favorable outcomes was 28 mm Hg (IQR 5-53) compared to 49 mm Hg (IQR 18-71) among patients with poor outcome. ? SBP was independently associated with higher (worse) mRS scores at discharge ( P  = .004) and at 90 d ( P  = .014) after adjusting for age, gender, and admission NIHSS. Every 10 mm Hg reduction in SBP from admission during EVT was associated with a 1.22-fold increase in the odds of having an unfavorable functional outcome at 90 d. The association between aSBP and outcome was also significant at discharge ( P  = .008) and 90 d ( P  = .014). CONCLUSION: Blood pressure reductions during EVT are common and lead to worse functional outcomes for patients affected by large-vessel acute ischemic stroke.